Accretion, underplating and exhumation along a subduction interface: From subduction initiation to continental subduction (Tavsanli zone, W. Turkey) - Plunder, A.; Agard, P.; Chopin, C.; Pourteau, Amaury; Okay, A. (2015)
© 2015 Elsevier B.V.. We herein reappraise the pressure-temperature (PT) evolution of the high-pressure and low-temperature (HP-LT) Tavsanli zone (western Turkey) in order to (i) better characterize rock units exhumed along a cooling subduction interface, from birth to steady state and (ii) constrain exhumation and detachment dynamics, as well as mechanical coupling between plates. Based on PT estimates and field observations three oceanic complexes are recognized between the HP-LT continental margin and the obducted ophiolite, with PT estimates ranging from incipient metamorphism to blueschist-facies conditions. PT conditions for the continental unit are reappraised to 24 kbar and ~ 500 °C on the basis of pseudosection modelling and Raman spectroscopy on carbonaceous material. A tentative reconstruction of the subduction zone evolution is proposed using available radiometric and palaeogeographic data and recent thermomechanical modelling. Both PT conditions and field observations point out to the slicing of km-sized units at different preferred depths along the subduction interface, thus providing constraints on the dynamics of accretion and underplating. In particular, the comparison of PT estimates for the Tavsanli zone and for other broadly similar fossil subduction settings (i.e., Oman, Corsica, New Caledonia, Franciscan, Schistes Lustrés) suggests that units are detached preferentially from the slab at specific depths of 30-40 km (i.e., downdip of the seismogenic zone) and ~ 80 km. We propose that these depths are controlled by major changes in mechanical coupling along the plate interface, whereas exhumation through time would rather be controlled by large-scale geodynamic boundary conditions.